2022
DOI: 10.3390/f13091353
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CBL-Interacting Protein Kinases’ Gene Family and Expression Pattern Reveal Their Important Roles in Response to Salt Stress in Poplar

Abstract: The CBL-interacting protein kinases’ (CIPKs) gene family plays an important role in plants under salt stress. In this study, a total of 31 PtrCIPK genes were identified in poplar. CIPKs’ gene family was divided into two categories, few intron classes and multi-intron classes. They all have the core components of the kinase domain and regulatory domain unique to the CIPK gene family and share most of the same motifs. PtrCIPKs have 17 fragment repeat events and have high homology with Arabidopsis thaliana and Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…However, our study found that GhCIPK23 showed a different expression pattern under salt stress than under other abiotic stresses and that this gene was significantly downregulated within the salt stress treatment period. The same results were observed in poplar and wheat [ 37 , 38 ]. In poplar, the gene expression of PtrCIPK1 , PtrCIPK5 , PtrCIPK8 and PtrCIPK18 showed an overall downward trend under salt stress [ 37 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, our study found that GhCIPK23 showed a different expression pattern under salt stress than under other abiotic stresses and that this gene was significantly downregulated within the salt stress treatment period. The same results were observed in poplar and wheat [ 37 , 38 ]. In poplar, the gene expression of PtrCIPK1 , PtrCIPK5 , PtrCIPK8 and PtrCIPK18 showed an overall downward trend under salt stress [ 37 ].…”
Section: Discussionsupporting
confidence: 82%
“…The same results were observed in poplar and wheat [ 37 , 38 ]. In poplar, the gene expression of PtrCIPK1 , PtrCIPK5 , PtrCIPK8 and PtrCIPK18 showed an overall downward trend under salt stress [ 37 ]. Under high salinity conditions, TaCIPK25 expression was markedly downregulated in roots.…”
Section: Discussionsupporting
confidence: 82%
“…Under the long-term stresses, we observed the elevated expression of several genes related to Ca 2+ -dependent signaling and protein phosphorylation. Among them are CNX1 and CRT , whose products act as molecular chaperones ( Liu et al., 2017 ; Joshi et al., 2019 ); CIPK12 and CIPK6 products bind to CBLs—which are regulators of Ca 2+ -signal transduction ( Sardar et al., 2017 ; Czolpinska and Rurek, 2018 ; Guo et al 2018 ; Bai et al., 2022 ). Additionally, several genes related to Ca 2+ -signaling were upregulated (Strap, SAPK3 , PXL1 , INPP5A2 , GRP , etc.…”
Section: Discussionmentioning
confidence: 99%
“…Under the long-term cold stress, we also observed the elevated expression of several genes, related to Ca 2+ -dependent signaling and protein phosphorylation in tea leaves. Among them, CNX1 (Calnexin) and calreticulin-like (CRT) which were reported to bind proteins on endoplasmic reticulum acting as molecular chaperones ( Liu et al., 2017 ; Joshi et al., 2019 ); also, CIPK12 and CIPK6 which were reported to bind CBLs regulating Ca 2+ -signal response ( Sardar et al., 2017 ; Czolpinska and Rurek, 2018 ; Bai et al., 2022 ). Additionally, several genes encoding the important components of membrane trafficking system and related to Ca 2+ -signaling were upregulated in tea plant under the long term cold stress, such as STRAP ( SERINE-THREONINE KINASE RECEPTOR-ASSOCIATED PROTEIN ) , SAPK3 ( SERINE/THREONINE-PROTEIN KINASE 3 ) , leucine-rich repeat receptor-like protein kinase PXY1 ( PHLOEM INTERCALATED WITH XYLEM-LIKE 1 ) , INPP5A2 type I inositol polyphosphate 5-phosphatase 2, glycine-rich protein A3-like GRP ( GLUTAMINE-RICH PROTEIN ), indicating their important roles in response to long-term cold stress in tea plant.…”
Section: Mechanisms Of Sensing and Signal Transduction Of Tea Plants ...mentioning
confidence: 99%